POWERPOINT SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB YANG MENARIK - Mahmudah, Ilvina Maulidiyah; Aulia, Farikhatul; Muhlashoh, A’malul; Hadiqi, Muhammad Musyaffak; Ahsanuddin, Mohammad (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Education in the modern era demands the use of technology to create a more interactive and interesting learning experience for students. PowerPoint is a technological tool that is a very useful tool in learning Arabic. In this article, we will explain the importance of PowerPoint in facilitating students' understanding and proficiency in various branches of Arabic language. By using PowerPoint, educators can convey learning material in a simple but interesting way, the teaching and learning process will feel more alive when an educator is able to create an exciting and fun teaching and learning atmosphere. Apart from that, it also allows students to more easily accept and master the lesson material.Keywords: Learning Media, PowerPoint, Arabic